AutoScan3D: A low-cost, portable photogrammetry system for automated 3D digitization of anatomical specimens - Rivera, Javier; Salinas, Paulo (PLOS ONE, 2025)
This study presents the development and preliminary validation of AutoScan3D, a portable and low-cost device for three-dimensional surface digitization of skulls using photogrammetry. The growing demand for accessible digitalization methods has encouraged the use of photogrammetry as a practical complement to high-end imaging technologies such as micro-computed tomography (micro-CT), which, although capable of visualizing internal structures with superior resolution, remains expensive and requires specialized facilities. AutoScan3D automates photographic capture through a smartphone camera, stepper motors, and an Arduino UNO controller. The system integrates a camera positioning module and an object rotation module to standardize image acquisition at fixed intervals. Its performance was evaluated by comparing the resulting 3D models with reference models derived from micro-CT scans to verify geometric accuracy and surface reconstruction fidelity. The results indicate that AutoScan3D reliably reproduces external morphology with realistic photographic textures and compact file sizes that facilitate subsequent manipulation in modeling software. Although its spatial resolution is lower than that of micro-CT, the device’s total hardware cost (≈USD 90) and ease of operation make it suitable for educational, demonstrative, and museographic contexts where external morphology is the main focus. Planned improvements include enhanced lighting control, compatibility with higher-resolution cameras, and a dedicated user interface. AutoScan3D thus provides a reproducible and affordable framework for surface-based three-dimensional digitization, expanding access to digital morphology tools in resource-limited settings.